Manajemen Program Vokasional dalam Meningkatkan Kualitas Peserta Didik - Muhammad Mahmud; Barnoto Barnoto (Pedir Research Institute, 2023)
This research was motivated by the condition of the HDI/IPM of the State of Indonesia being ranked 6th in Asean, the unemployment rate based on the highest high school education level, 80% of students did not continue their education and the need for good management skills program management. The problem formulation includes how to program skills, how to implement Skills Program management and what are the advantages and disadvantages of skills programs at MA NU Sunan Giri Prigen Kabupaten Pasuruan. This study has a purpose to describe the Skills Program, to analyze the implementation of Skills Program management and to analyze the strengths and weaknesses of the Skills Program. The research approach used is qualitative research with the type of research being case study research. The main instrument in this research is the researcher himself. The data obtained consisted of primary data and secondary data. Data collection techniques were obtained through interviews, observation and documentation. Data analysis consists of 3 (three) parts, namely data collection, data reduction, data presentation and drawing conclusions. The results of the study concluded that the Skills Program, starting from: Student selection, supporting facilities and infrastructure, teacher skills, Skills Program curriculum, Study time span, learning process, additional treatment outside and the existence of street vendors at the end of the program. The implementation of skills program management starts from planning, organizing, implementing and evaluating. Strengths and weaknesses of the Skills Program